ROLE OF PLANT GROWTH REGULATORS ATONIK AND HYPERTONIK IN REDUCING FLOWER DROPPING AND ITS AFFECT ON SEED YIELD - AL-Jobori, Kamil; EL-Bayaty, Ayyub (Iraqi Journal of Science, 2024)
The study was conducted during the winter season of 2004-2005 at tow locations , the first at the Experimental Station of Field Crop Department,College of Agriculture,Tikrit University. The second location was the Farms of Kifri city. The objective was to study the role of plant growth regulators Atonik and Hypertonik in reducing of flower dropping of tow broadbean cultivers(Local and Spanish), and its effect on seed yield .Asplit- split plot design was used with three replications. The main plots included the cultivers (Local and Spanish). The sub plot were the plant growth regulators(Atonik and Hypertonik). The sub-sub plots represented six dates of application: control(unapplication), soaking of seeds presowing in the solution of Atonik(1mL/L) and Hypertonik(0.5mL/L), spraying the plants at branch stage, beginning of bud formation, beginning of flowering, and beginning of pods formation. The soaking continued for 8 hours then seeds were dried at room temperature. The concentration of Atonik in spray solution was 400 mL/400Lof water, and Hypertonik was 200mL/400L of water.Agricultural practices were made according to recommendations.Results showed that local Cv. was superior over Espanish Cv.by 1.9 and 1.5%in leaf chlorophyll a and b content,respectively. Percentage of flower dropping of local Cv. Was reduced by 4 % and increased number of pods/plant and seed yield by 18 and 33.5 % , respectively. While Espanish Cv. Was superior in seed content of protein by 6.1%as a mean of two locations. Application of Hypertonik increased leaf content of chl.a , number of pods/plant and seed yield by 2.8, 8.6 and 10.8% in Tikrit location. While application of Atonik reduced flower dropping and increased number of pods/plant which reflected in increased seed yield by 9.9% in Kifri location. Application of PGR at the beginning of flowering increased leaf content of chl.a and b, number of pods/plant by 2.2, 2 and 2.2%, respectively, and reduced flower dropping by 6.3%, which reflected in increasing seed yild by 33.3%.on the other hand , application of PGR at the beginning of pod formation gave higher harvest index 54.4% and increased seed content of protein by 8.8% The interaction between study factors were significant in most studied charcters. In conclusion, the study suggested that the application of PGR at the beginning of flower reduced flowe dropping and increased seed yield. Atonik showed highest regulation of plant growth under salt conditions,especially when applied at the beginning of flowering. While Hypertonik showed highest regulation of plant growth under ordinary conditions.